Gambaran Kejadian Postpartum Blues pada Ibu Remaja di Sukowono, Jember - Mifta Irma Mei Liani; Dini Kurniawati; Lantin Sulistyorini (UPT Percetakan dan Penerbitan Universitas Jember, 2022)
Postpartum blues appear when someone does not successfully adapt to changes in life patterns due to pregnancy, labor and postpartum. Young mothers who are still not ready to be morally responsible often face mental turmoil due to still having an unstable mental attitude and immature emotions. The purpose of this study was to describe the incidence of postpartum blues in adolescent mothers in Sukowono District, Jember Regency. The research design used non-experimental research methods with descriptive research methods. The study was conducted on 34 postpartum teenage mothers using a total sampling technique. Data collection used EPDS questionnaire from January 2019 until February 2019. The results showed that postpartum teenage mothers as many as 10 respondents (29.4%) had the possibility of postpartum blues, 22 respondents (64.7%) occurred postpartum blues, 1 respondent (2.9%) experienced the possibility of postpartum depression, and 1 respondent (2.9%) experienced postpartum depression. The researchers describes that postpartum blues factors are age, parity, planning for pregnancy, level of education, occupation, socio-economic, tribe and type of labor in postpartum adolescent mothers. Important for nurses to optimize their role as educators and counselors to provide education and health information related to factors that influence the incidence of postpartum blues in adolescent mothers.